“Dosis de fertilizante granulado a base de micro elementos en el cultivo de tomate (lycopersicum esculentum) híbrido wsx 2205 F-1, en la provincia de Lamas” - Torres Llatas, Edson Rosbelth (2014)
This research was conducted at the farm ''The Pacific" located in the district and province of Lamas, San Martín department, with a geographical location of 76 º 30 '45 " west longitude, 06 º 20' 15" m.s.n.m.m south latitude and 835, in order to evaluate the yield and quality of tomato crop (Lycopersicum esculentum) Hybrid WSX 2205 F-1, compared to 4 doses of granulated fertilizer based on trace elements in the source Micromate Calcium Fortified). Also determine the cost of production for each treatment in a cost I benefit analysis. The MCF fertilizar doses studied were: No application (TO), 25 kg.ha-1 (T1), 50 kg.ha-1 (T2), 75 kg.ha-1 (T3) and 100 kg.ha-1 (T4) respectively for each treatment, fertilizer was applied one time eight days befare transplant to final field. Evaluations were made under a design Randomized Complete Blocks with five treatments and three replications. The best results for all evaluated variables was undoubtedly the T3 with the application of 75 kg.ha-1 of MFC, who reported a yield of 135 996, 44 kg.ha-1 compared to 25 506,79 Kg.ha-1 reported that the witness TO. Also awarded usa T3 B I C 4.3 with net profit of S /. 31 301,43 per hectare compared to the control TO where no profits are eamed, if not losses S l. 1 831,24 to hectare. Keywords: Micromate Calcium Fortified. Based micro granular fertilizar elements.